La Adopción de menores en el marco jurídico ecuatoriano - Castro-Núñez, Wilson Eduardo; Coronel-Piloso, Johanna Emperatriz; Loor-Miranda, Cristina Gabriela (IUSTITIA SOCIALIS, 2021)
La adopción de menores en el marco jurídico ecuatoriano